Periodization and physical performance in elite female soccer players - Mara, J. K.; Thompson, K. G.; Pumpa, K. L.; Ball, N. B. (International Journal of Sports Physiology and Performance, 2015)
Purpose: To investigate the variation in training demands, physical performance, and player well-being across a women`s soccer season. Methods: Seventeen elite female players wore GPS tracking devices during every training session (N = 90) throughout 1 national-league season. Intermittent high-speed-running capacity and 5-, 15-, and 25-m-sprint testing were conducted at the beginning of preseason, end of preseason, midseason, and end of season. In addition, subjective well-being measures were selfreported daily by players over the course of the season. Results: Time over 5 m was lowest at the end of preseason (mean 1.148 s, SE 0.017 s) but then progressively deteriorated to the end of the season (P < .001). Sprint performance over 15 m improved by 2.8% (P = .013) after preseason training, while 25-m-sprint performance peaked at midseason, with a 3.1% (P = .05) improvement from the start of preseason, before declining at the end of season (P = .023). Training demands varied between phases, with total distance and high-speed distance greatest during preseason before decreasing (P < .001) during the early- and late-season phases. Endurance capacity and well-being measures did not change across training phases. Conclusions: Monitoring training demands and subsequent physical performance in elite female soccer players allow coaches to ensure that training periodization goals are being met and related positive training adaptations are being elicited.